Michelia fulva Chang et B. L. Chen (Magnoliaceae Juss.) a new record for the flora of Vietnam - Nam, Vu Quang; NIAN-HE, XIA (Academia Journal of Biology, 2012)
During the examination on herbarium specimens of the family Magnoliaceae in herbaria of Vietnam and overseas countries, we paid attention to the flowering and fruiting Michelia specimens with collection numbers of L. V. Averyanov, P. K. Loc, N. X. Tam CBL 499; P. K. Loc, P. H. Hoang, L. V. Averyanov CBL 1420; D. K. Harder, N. T. Hiep, L. V. Averyanov, N. Q. Hieu 4943 which were collected from the forests of the remnant limestone karts Nam Linh Mts., belonging to Bao Lac District, Cao Bang Province and Sin Suoi Ho School, belonging to Quan Ba district, Ha Giang province, at ca. 1100-1600 m alt. They are being deposited in herbaria of the MusÐum National d’Histoire Naturelle (P), Institute of Ecology and Biological Resources (HN) and Missouri Botanical Garden (MO). Upon careful comparison with type specimens (SYS) and authenticated ones (IBSC), those specimens were identified as Michelia fulva Chang et B. L. Chen, a species first described from Maguan County, Yunnan Province, China where is nearly bordered on Vietnam. Vietnamese name is proposed as "Giæi l«ng n©u" to indicate the brown indumentum on its leaf buds, below surfaces and twigs. With this new record of Michelia fulva, totally 21 Michelia species of the family Magnoliaceae are heretofore recognized from Vietnam.